Pernix Central - Salas-Mejías, Erwin (Instituto Tecnológico de Costa Rica, 2018)
This document consists of a detailed report on the graduation work carried out to opt for the bachelor's degree in computing, the purpose of the project is to contribute to the management of the information of the Pernix company through a software platform. With the goal of making easier the administration of the company's projects as well as its clients and associated teams, activities carried out and list of employees labeled with their technical and soft skills and other functions that are explained in detail throughout the document. During the project development process several stages were addressed such as requirements collection, design, development and evaluation of the platform using methodologies such as user histories, flow diagrams, interface and scrummating for the development divided into several stages. As a final result, a quality product was obtained according to the requirements established in the meetings with those involved.
Práctica Profesional (Bachilerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2018.
Keywords: Software; Automatización; Flujo de datos; Bases de datos; Computación; Políticas; Información; Research Subject Categories::TECHNOLOGY